Event-triggered control of spatially distributed processes via unmanned aerial vehicle. (14th November 2016) - Lou, Xuyang; Jiang, Zhengxian
This article concerns the problem of event-triggered observer-based output feedback control of spatially distributed processes under the autonomous operation of an unmanned aerial vehicle. The specific spatially distributed process is modeled within the distributed parameter systems framework. To control the considered distributed parameter system efficiently, we first estimate the states with an observer based on the measurement information from sensors. Then, an event-triggered observer-based controller is designed, which can reduce the frequency of signal transmissions between the observer and the controller. In contrast to normal sampled-data controller that is updated periodically, the event-triggered controller is updated only when an "event" happens. Moreover, the Zeno behavior is also excluded by proving there exists a lower bound for interexecution time. Numerical simulations are finally presented to illustrate the effectiveness of the proposed control method.